Inadequate and Incomplete: Chinese Newspapers' Coverage of the First Licensed Human Papillomavirus (HPV) Vaccine in China. Issue 6 (3rd June 2018) - Li, Wenbo; Nowak, Glen; Jin, Yan; Cacciatore, Michael
Abstract : Glaxo Smith Kline's Cervarix was the first human papillomavirus (HPV) vaccine licensed for use in China and officially launched there on 31 July 2017. Since news media content can influence people's vaccine-related knowledge, understanding, and intentions, a content analysis was used to examine Chinese newspapers' coverage of the HPV vaccine. A total of 253 articles published from 2000 to 2016 met the inclusion criteria and were coded. The results show that HPV and the HPV vaccine received very little newspaper coverage in China both before and after vaccine licensure. Most of the coverage came from China Party press newspapers, with the stories predominantly using thematic rather than episodic framing. Application of the Health Belief Model to the content analysis revealed that benefits, self-efficacy, and cues to action were found in most news stories. Overall, given the relative lack of Chinese newspaper coverage, public health officials and health-care providers in China should assume most people, including those for whom HPV vaccination is recommended, have little or no knowledge about HPV, HPV vaccine, and the reasons for the vaccination recommendation. If news media are to be a source of HPV information for the Chinese public, significant efforts will be needed to increase attention.